Determinants of Dental Service Utilization Among 2 to 11-Year-Old California Children - Umo Isong, DDS, MPH, PhD; Jane A. Weintraub, DDS, MPH (Blackwell Synergy, 2005)
The 2001 California Health Interview Survey (CHIS} was designed to elicit population-based estimates about health care access and insurance coverage.